The Global Health Research Capacity Strengthening (GHR-CAPS) Program: trainees’ experiences and perspectives - Lisa Merry; Anne-Marie Turcotte-Tremblay; Nazmul Alam; Nicole D’souza; Myriam Fillion; Federica Fregonese; Lara Gautier; Kadidiatou Kadio (Journal of Global Health Reports)
# Introduction